The Chaos of Polish Space and Sir Roger Scruton - Nawrocki, Tomasz (Roczniki Nauk Społecznych, 2023)
Sir Roger Scruton disapproved of the changes to urban space initiated by modernism in the 20th century. In his writings on aesthetics, his journalism, and his social activism, he consistently argued for restoring the ‘real’ city, in which the community of inhabitants decides. This text aims to trace Scruton’s argument and use it to explain the spatial chaos in Poland. From Scruton’s multifaceted work, I limited myself to three elements related to the critique of modernism, the architect’s role and the problem of the city’s identity and its inhabitants. This was to show a conservative way to change the situation in the city. This conservative remedial programme consists of giving the city back to the community of inhabitants, rebuilding public space (treated as a common good) and insisting on certain norms which, in the interest of the community, will limit the laissez-faire approach to space, are fundamental issues whose implementation can influence the variation of Polish space.